1997
DOI: 10.1002/(sici)1098-1063(1997)7:1<48::aid-hipo5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro electrophysiology of rat subicular bursting neurons

Abstract: Intracellular recordings were used to study the electrophysiological properties of rat subicular neurons in a brain slice preparation in vitro. Cells were classified as bursting neurons (n = 102) based on the firing pattern induced by depolarizing current pulses. The bursting response recorded at resting membrane potential (−66.1 ± 6.2 mV, mean ± SD n = 94) was made up of a cluster of fast action potentials riding on a slow depolarization and was followed by an afterhyperpolarization. Tonic firing occurred at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
(56 reference statements)
3
37
0
Order By: Relevance
“…This result was consistent with that obtained from previous in vitro studies (20, 34, 48). The firing rate of irregular discharge neurons under urethane anesthesia observed in our experiments was similar to that of the freely moving state (2), but was lower than that in slice preparation (19, 37).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result was consistent with that obtained from previous in vitro studies (20, 34, 48). The firing rate of irregular discharge neurons under urethane anesthesia observed in our experiments was similar to that of the freely moving state (2), but was lower than that in slice preparation (19, 37).…”
Section: Resultssupporting
confidence: 93%
“…Our results show that on the basis of patterns of electrical activity, subicular neurons can be divided into three groups: bursting, regular discharging, and irregular discharging cells, which is similar to the classification used in freely-moving rats (2, 47). A similar classification of subicular neurons into bursting neurons, regular-spiking neurons, and fast irregular-spiking neurons was adopted in in vitro experiments (20, 34, 35, 38, 48, 50, 57, 59). However, there is a large discrepancy in the percentages of these three types of neurons between this report and previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that rat subicular pyramidal neurons exhibit two types of discharge patterns in response to intracellular stimulation: regular spiking and burst firing (Mattia et al 1997; Staff et al 2000; Menendez de la Prida et al 2003). The burst firing is generally featured with a cluster of action potentials at frequencies of ∼200 Hz and is thought to result from high voltage‐activated Ca 2+ currents (Jung et al 2001; but see Mattia et al 1997). In our experiments, mouse subicular pyramidal neurons of thick slices also exhibited two types of discharge patterns following intracellular stimulation (depolarizing current pulses of 200–500 pA, 0.5–1 s).…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic bursting, reportedly, is more abundant in the latter types of neurons than in CA1 pyramidal cells (Wong et al, 1979;Mattia et al, 1997;Staff et al, 2000). In both adult CA3 and subicular pyramidal cells, the spike ADPs and associated bursting have been attributed to a Ca 2ϩ spike aftercurrent (Wong and Prince, 1981;Jung et al, 2001), although a contribution of an Na ϩ spike aftercurrent to these potentials has not been excluded (Mattia et al, 1997).…”
Section: Persistent Namentioning
confidence: 99%